2022
DOI: 10.3390/jpm12050847
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of Retinal Drusen in Subjects at High Genetic Risk of Developing Sporadic Alzheimer’s Disease: An Exploratory Analysis

Abstract: Having a family history (FH+) of Alzheimer’s disease (AD) and being a carrier of at least one ɛ4 allele of the ApoE gene are two of the main risk factors for the development of AD. AD and age-related macular degeneration (AMD) share one of the main risk factors, such as age, and characteristics including the presence of deposits (Aβ plaques in AD and drusen in AMD); however, the role of apolipoprotein E isoforms in both pathologies is controversial. We analyzed and characterized retinal drusen by optical coher… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 48 publications
0
7
0
Order By: Relevance
“…Also, retinal amyloid/inclusion bodies indicated in AD [ 72 , 73 ] are also found in retinal drusenoid structures in age-related macular degeneration (AMD) [ 74 ]. It must however be noted that other studies have found no association between a family history of AD/APOE e4 genotype and the presence of drusen, and that amyloid deposits are distinct from drusenoid structures [ 72 , 75 ]. Without a multimodal imaging model of blue autofluorescence imaging, color fundus, and spectral domain OCT, drusenoid structures in AMD may be falsely counted as retinal amyloid or inclusion bodies.…”
Section: Discussionmentioning
confidence: 99%
“…Also, retinal amyloid/inclusion bodies indicated in AD [ 72 , 73 ] are also found in retinal drusenoid structures in age-related macular degeneration (AMD) [ 74 ]. It must however be noted that other studies have found no association between a family history of AD/APOE e4 genotype and the presence of drusen, and that amyloid deposits are distinct from drusenoid structures [ 72 , 75 ]. Without a multimodal imaging model of blue autofluorescence imaging, color fundus, and spectral domain OCT, drusenoid structures in AMD may be falsely counted as retinal amyloid or inclusion bodies.…”
Section: Discussionmentioning
confidence: 99%
“…AMD is associated with the accumulation of degenerative material called drusen between the RPE and its basement membrane, eventually leading to a degeneration of overlying photoreceptors. Pathological examination of drusen has shown the presence of Aβ protein, suggesting a link with AD [17,18]. Glaucoma is a progressive ocular condition characterized by loss of RGC and thinning of its axons, the retinal nerve fiber layer (RNFL) of the retina.…”
Section: Ad Macular Degeneration and Glaucoma: Common Pathogenetic Me...mentioning
confidence: 99%
“…Sustained elevation of IOP leads to slowing of axonal conduction within RNFL, causing accumulation of Aβ and p-tau in RGCs, resulting in neuronal degeneration. Loss of RGC leads to axonal loss, thinning of RNFL, and optic atrophy, which leads to blindness [18,19].…”
Section: Ad Macular Degeneration and Glaucoma: Common Pathogenetic Me...mentioning
confidence: 99%
“…Abnormalities on OCTA images usually indicate the presence of a number of diseases, such as early glaucomatous optic neuropathy [1], diabetic retinopathy [2], and age-related macular degeneration [3]. Some other recent studies have shown that deep microvascular morphological changes revealed by OCTA images are associated with Alzheimer's disease [4] and mild cognitive impairment [5]. This opens up new ideas to investigate the relationship between abnormalities in retinal vessels and various neurodegenerative diseases.…”
Section: Introductionmentioning
confidence: 97%
“…Mse loss 3. Mse loss + contrastive loss 4. Mse loss + contrastive loss + image augmentation (CLANE) 5.…”
mentioning
confidence: 99%